Evaluation of an Outdoor Pilot Scale Hybrid Growth Algal-Bacterial System for Wastewater Bioremediation - Hassan, Khalid; Khalifa, Abdelkawi; Hegazy, Mohamed; Helmy, Mohamed (Civil Engineering Journal, 2024)
Synergistic cooperation and interaction between algae and bacteria had made it easy by using one single step only to efficiently eliminate the impurities found in wastewater. High pollution levels triggered by the disposal of untreated wastewater and the harsh social and economic conditions, together with high construction and operation costs of conventional wastewater treatment systems, made it vital to find simple, efficient, cost-effective treatment systems. In this research work, a hybrid microalgae-bacteria pilot outdoor system comprised of a series of Algaewheel® rotating algae contactors (RACs) that receive preliminary treated domestic wastewater at a hydraulic retention time (HRT) of 8 hours was monitored for a period of 5 months. An average dissolved oxygen (DO) value of 3.04 ± 1.02 mgL⁻¹ was obtained in the effluent-treated wastewater. While the average removal efficiencies recorded for the parameters monitored were 90.73% for BOD5, 89.10% for COD, 93.45% for TSS, 77.05% for NH3-N, and 70.40% for TN. All the effluent values for the parameters monitored were below the limits of both the local and international standards. The pilot system was found to be suitable and adaptable for small communities with low discharges of 5000 m³/day or less due to its low operation and maintenance requirements, as its electricity consumption is 80% less compared with the conventional wastewater treatment systems. Doi: 10.28991/CEJ-2024-010-11-09 Full Text: PDF